How do we fit underground coal mining work boots?. Issue 11 (2nd November 2018) - Dobson, Jessica A.; Riddiford-Harland, Diane L.; Bell, Alison F.; Steele, Julie R.
Abstract: Acceptable footwear fit, particularly width, is subjective and vaguely quantified. Proper shoe fit is important because it affects both comfort and the potential to prevent injury. Although mismatches between the feet of underground coal miners and their internal boot dimensions are known, no research has been undertaken to determine the impact of these mismatches on worker perceptions of fit, comfort and pain. This study aimed to quantitatively assess mining work boot fit relative to underground coal miners' subjectively rated work boot fit and comfort, reported foot problems, lower limb pain and lower back pain in order to develop evidence-based work boot fit recommendations. Traditional footwear fitting methods based predominantly on foot length are insufficient for underground coal mining-specific footwear. Instead, fit at the heel, instep and forefoot must be considered when fitting underground coal mining work boots, in conjunction with the traditional length measurement.Practitioner summary: Underground coal miners report their work boots fit but are uncomfortable. This study assessed actual fit relative to perceived fit, comfort, foot problems, lower limb pain and lower back pain of 197 miners. Fit at the heel, instep and forefoot must be considered when fitting mining work boots.